TED-TALK: A SUPPLEMENT MATERIAL TO PROMOTE STUDENTS’ AUTONOMY IN LISTENING - Dian Puspita; Dina Amelia (Eltin Journal : Journal of English Language Teaching in Indonesia, 2020)
This paper explores the use of TED (technology, Entertainment, and Design) Talk in promoting students’ learning autonomy and enhancing English learners’ listening skill, especially in ESL. This research uses mixed method; qualitative descriptive to find out students learning autonomy and students’ perception on the use of TED-Talk, and quantitative descriptive to find out students’ listening score improvement. The respondents of the study are students who were taking the English for Business course even semester of the 2019/2020 academic year at the Indonesian Technocrat University (UTI).The data were gathered through questionnaires and test. The results show that students’ learning autonomy is increasing in terms of learner control, critical reflection, motivation, and information literacy. By using TED-Talk, it is also shown that students’ listening score is increasing even though just slightly. Furthermore, it is found that students’ perception toward the use of TED-Talk is also positive. It gives the good implication in the future that they will continue using it as their additional learning material in listening. The consistence of students’ autonomy in learning will significantly improve students’s comprehension level.   Keywords: autonomy, listening, students’ perception, supplement materials, TED-talks